2018
DOI: 10.3390/en11051188
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of Predicting Daily Solar Radiation Using Bat Neural Network (BNN), Generalized Regression Neural Network (GRNN), and Neuro-Fuzzy (NF) System: A Case Study

Abstract: Highly accurate estimating of daily solar radiation by developing an intelligent and robust model has been a subject of prominent concern for many researchers in the past few years. The precise prediction of solar radiation is of great interest and importance to improve the incorporation of solar power plants. In this study, a novel multilayer framework for a particular combination of the bat algorithm (BA) and neural networks (NN) is proposed, which is called bat neural network (BNN), aimed at predicting dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 52 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…The proposed hybrid metaheuristic LSSVM-BA algorithm is used for the prediction of DO concentration. The BA has been widely utilized for parameter optimization of the model used in forecasting climatological variables [62,63] and reservoir operation [64,65]. The studies reported BA as an efficient optimization technique.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed hybrid metaheuristic LSSVM-BA algorithm is used for the prediction of DO concentration. The BA has been widely utilized for parameter optimization of the model used in forecasting climatological variables [62,63] and reservoir operation [64,65]. The studies reported BA as an efficient optimization technique.…”
Section: Introductionmentioning
confidence: 99%
“…Lotfinejad et al . demonstrated bat neural network, which uses a novel multilayer framework for a particular combination of the bat algorithm (BA) and a three‐layer artificial neural network (ANN) to estimate daily solar radiation over Iran. The parameters of ANN can be optimized by BA.…”
Section: Introductionmentioning
confidence: 99%
“…Crop cultivation is difficult to model as it is a complex and nonlinear process. Soft-computing approaches have revealed efficient solutions for nonlinear natural process such as flood, drought, wind, and rainfall (Asadi, Shahrabi, Abbaszadeh, & Tabanmehr, 2013;Fortin, Anctil, Parent, & Bolinder, 2010;Gago, Martínez-Núñez, Landín, & Gallego, 2010;Lotfinejad et al, 2018;Moazenzadeh, Mohammadi, Shamshirband, & Chau, 2018;Mosavi, Bathla, & Varkonyi-Koczy, 2017;Nazari & Shamshirband, 2018;Sehgal, Sahay, & Chatterjee, 2014;Tiwari & Chatterjee, 2011). Some of the previous works have used soft-computing method for solving problem related to agriculture industry.…”
Section: Introductionmentioning
confidence: 99%